Literatur Riview Tantangan Dan Strategi Implementasi Resolusi Dalam Konflik Global - Nova Kharisma; Nadila Dwi Firda Kutsyah; Siti Aminatus Zuhriyah; Riskiatul Kamilah; Mu’alimin (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This article is a literature review study. Research using this literature review study is research where all information is obtained from journal articles and books. The results of this literature review research show that there are several challenges, strategies, obstacles and approaches to conflict resolution. The challenges of global conflict resolution are cultural and linguistic differences, as well as economic and religious differences. The strategy in conflict itself is commitment and negotiation, misunderstanding, as well as strong and neutral strategies. The obstacles experienced in its implementation are differences in opinion, culture and management. There is also dissatisfaction when conflict resolution is implemented. There is a conflict resolution approach.